Memories of the Future: Traditional Russian Economic and Environmental Practices in New Foreign Policy Conditions. Article two. Arctic Development - A. D. Khlutkov; V. A. Shamakhov; N. M. Mezhevich (Управленческое консультирование, 2022)
Fundamental economic and political changes at the beginning of 2022 force us to revise or refine traditional approaches to issues of national economic development. The growing conflict leads to the fact that attention to the Arctic as a region is constantly increasing. The risks of economic interference of non-Arctic countries in the affairs of Russia have significantly increased. The ecology of the Arctic is becoming the subject of international speculation.